Harnessing 3D printing in bone tissue engineering - Suchitra Nishal; Parmita Phaugat; Reena Devi; Vandana Garg; Virender Kumar; Hitesh Chopra; Navidha Aggarwal (Discover Materials)
Abstract Background The purpose of the current study is to describe the technological, functional, and regulatory aspects of 3D printing. It also discusses the challenges and future aspects of 3D printing. The process of digital fabrication, commonly known as 3D printing or additive manufacturing, involves gradually adding materials to a geometric representation to produce actual items. In the fields of agriculture, healthcare, industries, 3D printing is being used more and more for mass modification and manufacture of any kinds of open source design. In tissue engineering, 3D printing is a crucial tool for creating intricate frameworks using biocompatible materials, cells, and supporting elements. Methods With the use of the keywords 3D printing, Stereolithography, Fused deposition modelling, tissue scaffolds, and regulatory considerations, searches were conducted in the databases Pubmed, Medline, and Google Scholar. Studies that included technological, functional, and future factors were found and given more consideration. Results This review covered every class of 3D printing and their relative importance. Tissue engineering and tissue scaffolds have been thoroughly addressed in relation to applications of 3D technology to define the use of 3D printing. The regulatory elements of 3D printing have also been discussed, along with the challenges and potential outcomes. Conclusion The technological, functional, and regulatory implications of 3D printing were discussed in the current study. Graphical Abstract